Arachidonic acid release mediated by OX(1) orexin receptors - Turunen, Pauli M (Blackwell Publishing Ltd, 2010)
BACKGROUND AND PURPOSE: We have previously shown that lipid mediators, produced by phospholipase D and C, are generated in OX(1) orexin receptor signalling with high potency, and presumably mediate some of the physiological responses to orexin. In this study, we investigated whether the ubiquitous phospholipase A(2) (PLA(2)) signalling system is also involved in orexin receptor signalling. EXPERIMENTAL APPROACH: Recombinant Chinese hamster ovary-K1 cells, expressing human OX(1) receptors, were used as a model system. Arachidonic acid (AA) release was measured from (3)H-AA-labelled cells. Ca(2+) signalling was assessed using single-cell imaging. KEY RESULTS: Orexins strongly stimulated [(3)H]-AA release (maximally 4.4-fold). Orexin-A was somewhat more potent than orexin-B (pEC(50)= 8.90 and 8.38 respectively). The concentration–response curves appeared biphasic. The release was fully inhibited by the potent cPLA(2) and iPLA(2) inhibitor, methyl arachidonyl fluorophosphonate, whereas the iPLA(2) inhibitors, R- and S-bromoenol lactone, caused only a partial inhibition. The response was also fully dependent on Ca(2+) influx, and the inhibitor studies suggested involvement of the receptor-operated influx pathway. The receptor-operated pathway, on the other hand, was partially dependent on PLA(2) activity. The extracellular signal-regulated kinase, but not protein kinase C, were involved in the PLA(2) activation at low orexin concentrations. CONCLUSIONS AND IMPLICATIONS: Activation of OX(1) orexin receptors induced a strong, high-potency AA release, possibly via multiple PLA(2) species, and this response may be important for the receptor-operated Ca(2+) influx. The response coincided with other high-potency lipid messenger responses, and may interact with these signals.